[8(y + 5) - 16] - [3(y - 3) + 3]

Now first we solve the small brackets, we get

= [8y + 40 - 16] - [3y - 9 + 3]

Now

= [8y + 24] - [3y - 6]

Now we open the brackets and the signs will change in the second bracket because of minus sign outside, then

= 8y + 24 - 3y + 6

separating like terms , we get

= 8y - 3y + 24 + 6

= (8 - 3)y + 30

= 5y + 30

Or

= 5(y + 6)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up